1997
DOI: 10.1037/1076-8998.2.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work overload and burnout on cholesterol and triglycerides levels: The moderating efffects of emotional reactivity among male and female employees.

Abstract: The effects of objective and subjective overload, and of physical and emotional burnout, on cholesterol and triglycerides levels were studied in a quasiprospective design. The possible moderating effects of emotional reactivity on these relationships were also investigated. The study's hypotheses were tested separately for male and female employees. Time 1 (T1) data were collected from 665 healthy employees (30% women) while they were undergoing periodic health examinations in a health-screening center. Time 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 55 publications
1
105
1
3
Order By: Relevance
“…This indicated that although the mother and father may have several shared concerns regarding the child and the family, these shared concerns were not the main or only source of burnout symptoms. The higher levels of burnout among women compared with men are in line with previous findings in other settings (Lindblom, Linton, Fedeli, & Bryngelsson, 2006;Shirom et al, 1997). This difference may reflect a gender typical style in responding to the questionnaire.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This indicated that although the mother and father may have several shared concerns regarding the child and the family, these shared concerns were not the main or only source of burnout symptoms. The higher levels of burnout among women compared with men are in line with previous findings in other settings (Lindblom, Linton, Fedeli, & Bryngelsson, 2006;Shirom et al, 1997). This difference may reflect a gender typical style in responding to the questionnaire.…”
Section: Discussionsupporting
confidence: 81%
“…One of the most widely studied aspects of stress-related psychological exhaustion is burnout. The burnout syndrome, a constellation of symptoms including physical, emotional and cognitive exhaustion, is a consequence of longstanding stress exposure (Melamed, Kushnir, & Shirom, 1992;Shirom, Westman, Shamai, & Carel, 1997). Originally regarded as exclusively an effect of work stress (Maslach, Schaufeli, & Leiter, 2001), burnout may follow long-term stress irrespective of its source (Swedish National Board of Health and Welfare, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Burnout is known to occur in professions with frequent, stressful interpersonal interactions and can lead to decreased effectiveness at work, negative health outcomes, and less job satisfaction [5,17,18,30]. A relationship between burnout and job satisfaction is established for several types of physicians [1,4,8,10,14,19,26,27], but has been studied less among surgeons treating musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…People who do stressful work build psychological and organizational resources to help manage the stress [15]. This can be difficult to maintain, and surgeons are susceptible to stress-related diseases (ie, depression and addiction), burnout, and dissatisfaction [5,17,30]. To help build and maintain resources to limit burnout and optimize job satisfaction among surgeons treating musculoskeletal conditions, it would help to have a better understanding of the associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…For individuals, burnout has been tied to numerous health related complications including anxiety, depression, and diminished psychological well-being, amongst others (Cordes & Dougherty, 1993;Kahill, 1988;Maslach, 1982;Maslach, 1993;Shirom, Westman, Shamai, & Carel, 1997;Wright & Bonnet, 1997;Wright & Hobfoll, 1994). Similarly, in the organizational context burnout has been linked to deviant behavior, turnover, decreased employee commitment, poor morale, poor quality of care in health services institutions, loss of management potential, and job dissatisfaction (Chullen, Dunford, Angermeier, Boss & Boss, 2010;Jackson, Schwab, & Schuler, 1986;Leiter & Maslach, 1988;Wolpin, Burke, & Greenglass, 1991).…”
Section: Introductionmentioning
confidence: 99%